ANALISIS PENDAPATAN USAHATANI PADI SAWAH (Oryza sativa L.) DI DESA MAKROMAN KECAMATAN SAMBUTAN KOTA SAMARINDA (Income Analysis of Wetland Paddy Farming (Oryza sativa L.) in Makroman Village Sambutan Subcity Samarinda City) - CHRISTIAN ELFRADO SIMATUPANG; NIKE WIDURI (Universitas Mulawarman (University of Mulawarman), 2018)
The purposes of this study were to determine the production costs of paddy farming, revenue, and the amount of income of wetland paddy farmers in Makroman Village, Sambutan Subcity. The research was conducted from April to June 2018. The data needed in this study were primary data and secondary data. The sampling method was probability sampling technique that was proportionate stratified random sampling by using the Slovin formula with 35 respondents. Data analysis calculated total costs, revenue, and income. The results showed that the total production costs spent by farmers was IDR125,763,960.00 cropping season (cs)-1 with an average of IDR3,593,256.00 respondent-1 cs-1, and IDR213,007,735.73 ha-1 cs-1 with an average of IDR6,085,935.31 ha-1 cs-1 respondent-1. Revenue was as much as IDR768,600,000.00 cs-1 with an average of IDR21,960,000.00 cs-1 respondent-1 and IDR1,226,383,333.33 ha-1 cs-1 with an average of IDR35,039,523.81 ha-1 cs-1 respondent-1. Paddy farming income was IDR642,836,040.00 cs-1 with an average of IDR18,366,744.00 cs-1 respondent-1 and IDR1,010,375,597.60 ha-1 cs-1 with an average of IDR28,867,874.22 ha-1 cs-1 respondent-1 for planting area of 0.643 ha.